Kecepatan Adopsi Program Fasilitasi Hak Kekayaan Intelektual Merek Dagang untuk Usaha Kecil Menengah - Fadzriani Nur; Sarwititi Sarwoprasodjo; Musa Hubeis (Institut Pertanian Bogor, 2016)
Small-medium enterprises (SME) is a sectors who get special attention from Indonesia Government to face ASEAN Economic Community (AEC). Bandung is a city in West Java with a good growth on SME. But, SME have not awareness on their product legality. So, Bandung Government, make collaboration with State Minister for Small and Medium Enterprises and Trade Industry and Ministry of Justice and Human Rights Bandung City, to make a new programs for protecting SME in Bandung. This purpose of this research were: (1) to know the adoption rate of trademark IPR facilitation programs in Bandung, (2) to analyze the factors can influence SME to take a decision for adopt the fasilitation programs of trademark intellectual property rights (IPR) for SME, and (3) to analyze the effect SME chararacteristic toward adoption rate of trademark IPR facilitation programs in Bandung, and Research was conducted in Bandung, since in June 2015 to April 2016. The results showed adoption rate in IPR trademark facilitating program, that most of SMEs registering IPR trademark were late majority. Around 51.50 percent of respondents registered on September and October 2014. Attribute of innovation are have influenced to take a decision, so give influenced too for adoption rate this program. But communication channel and communicator did not influence rate of adoption. SMEs characteristic did not influence significantly adoption rate of the program